Factors Contributing to Intradialytic Hypertension in Hemodialysis Patients - Armiyati, Yunie; Hadisaputro, Suharyo; Chasani, Shofa; Sujianto, Untung (South East Asia Nursing Research, 2021)
Intradialytic hypertension (IDH) is the most common complication of hemodialysis patients in Indonesia. It must be controlled, to maintain the patient's quality of life and prevent worsening conditions. Some factors affecting IDH include predialysis fluid overload characterized by excessive interdialytic weight gain (IDWG), low adherence to fluid restriction and increased ultrafiltration during haemodialysis. The study aims to identify contributing factors of IDH. A case-control design was used in this study. A purposive sampling technique was used to recruit 92 samples at two centres of dialysis in Semarang, which was divided into case group (n=46) and control group (n=46). Data were analyzed using the Chi-square test by calculating Odds Ratios (OR). The finding showed that excessive IDWG (p=0,000, OR=16.95, 95% CI:5,56-51,65), low fluid adherence (p=0,001, OR=4,41, 95% CI:1,82-10,68) and excessive ultrafiltration (p=0,000, OR = 29,52, 95% CI:9,23-94,46) showed significant result. However, the incidence of IDH was not correlated with sex, age and length of haemodialysis. A greater increase in interdialytic weight requires lower fluid and higher ultrafiltration factors must be controlled precisely because those are considered as the risk factors for the high incidence of IDH. Excessive ultrafiltration is the most dominant risk factor in the high incidence of IDH.